Estrategias motivacionales en el proceso educativo para el interaprendizaje del área de matemática de los estudiantes de cuarto y quinto año de Educación General Básica de la Escuela Juan Celio Secaira del cantón Chimbo provincia Bolívar, durante el periodo 2010-2011 - Cáliz Romero, Angel Dionicio (2012)
To fulfill the different phases that characterize to the present investigation work you base us on the different factors that affect and to apply “Strategies motivacionales in the educational process in the area of the room students' mathematics and fifth year of Basic General Education of the School Juan Celio Secaira of the Canton Chimbo County Bolívar, period 2010-2011. The investigation had as purpose to know on the motivation in the childhood in the educational process if the orientation of the educational ones is adapted and applied the students on time so that these it contributes to a good motivation from the school based in technical motivational, to stimulate the being's niño/a attitude and to drive to be active entities in the society. It is necessary to indicate that the motivation in the childhood, to other of the family parents partly is responsibility of the educational system because they pass 40% in and of itself in the educational institutions the maestros/as they are in the duty of working motivating so that the boy sits down pleasure for the mathematics helping to improve the superación process. In the I surrender I we make emphasis to the theoretical mark and we refer some terms based in theoretical notebooks and philosophical focuses with respect to the motivation that allows to make emphasis to the variables as the substantial part of the working process of grade like support the motivation guided to the improvement of the educational process in the area of the students' mathematics transformed into active entities and participativos demonstrating the change that if one can make evident in the classroom. In the I surrender II we have the methodological strategies that he/she helps us to sustain, he/she administers and to exercise a pursuit and control of the whole investigative process; on the technical motivacionales in the educational process. The applied instruments you viabilizaron for the use of descriptive, analogical or comparative, deductive, inductive method, the method lúdico and the logical historical method. It is also described next the gathering process and analysis of data by means of the managed surveys and applied to educational and students the same one that was constituted by 74 students, of which 14 are educational that they work in the school and 60 are niños/as that the room and recruit study year of Basic General Education. The survey, the interview, the direct observation has been the most important pedestal for the obtaining of the information that has allowed us to do with clarity the true problem, by means of the quantitative and qualitative analysis. Regarding the sources of gathering of data, these they revealed important results that were analyzed and confronted, those which abalizan the investigation of the outlined problem. I surrender III analysis and interpretation of the results this work it has a statistical information, the contents are in charts of distribution of frequencies and graphics, supported in their respective analyses. Of this content we have elaborated the summations and pertinent recommendations, he/she stops then to give a solution alternative to the problem outlined through a viable and novel proposal with technical motivational and innovators. For the confirmation of the hypothesis he/she made it to him through a simple descriptive statistical process, specifying their interpretation; and we have ended up establishing that the strategies motivacionales contribute to the educandos like a fundamental pillar in the educational process. In this sense the thesis proposal allowed to take decisions to give a solution elaborating an informative mark of techniques to motivate the students in mathematics's area with which seek to change the working system being participativo, asset allowing them to assume responsibilities and be main characters of its own learning.